Political and historical encyclopedia of women - Fauré, Christine; Dubois, Richard (Routledge, 2003)
The original French edition of this encyclopedia has been lauded by French reviewers, and now Routledge is proud to publish this acclaimed resource in an English language edition.
Originally published: Encyclopédie politique et historique des femmes. Paris : Presses Universitaires de France, 1997.
Keywords: Women -- Political activity -- Europe.; Women -- Political activity -- North America.; Women legislators -- Europe.; Women legislators -- North America.; Women's rights -- Europe -- History.; Women's rights -- North America -- History.; Women -- North America -- History -- Encyclopedias.; Women's rights -- Europe -- History -- Encyclopedias.; Women's rights -- North America -- History -- Encyclopedias.; Feminism -- Europe -- History -- Encyclopedias.; Feminism -- North America -- History -- Encyclopedias.; Women -- Europe -- History -- Encyclopedias.; Femmes en politique -- Europe -- Histoire -- Encyclopédies.; Femmes en politique -- Amérique du Nord -- Histoire -- Encyclopédies.; Femmes -- Europe -- Histoire -- Encyclopédies.; Femmes -- Amérique du Nord -- Histoire -- Encyclopédies.; Femmes -- Droits -- Europe -- Histoire -- Encyclopédies.; Femmes -- Droits -- Amérique du Nord -- Histoire -- Encyclopédies.; Féminisme -- Europe -- Histoire -- Encyclopédies.; Féminisme -- Amérique du Nord -- Histoire -- Encyclopédies.; Femmes -- Activité politique -- Europe.; Femmes -- Activité politique -- Amérique du Nord.; Femmes -- Droits -- Europe -- Histoire.; Femmes -- Droits -- Amérique du Nord -- Histoire.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; POLITICAL SCIENCE -- Essays.; Women; Feminism; Women legislators; Women -- Political activity; Women's rights; Europe; North America; encyclopedias.; Encyclopedias; History; Encyclopedias.; Encyclopédies.